Decision-Making in Breast Cancer Surgery: Where Do Patients Go for Information?. Issue 5 (May 2016) - Schmidt, Hank; Cohen, Almog; Mandeli, John; Weltz, Christina; Port, Elisa R.
Patient decision-making regarding breast cancer surgery is multifactorial, and patients derive information on surgical treatment options from a variety of sources which may have an impact on choice of surgery. We investigated the role of different information sources in patient decision-making regarding breast cancer surgery. Two hundred and sixty-eight patients with breast cancer, eligible for breast-conserving therapy were surveyed in the immediate preoperative period, and clinical data were also collected. This survey evaluated the scope and features of patient-driven research regarding their ultimate choice of surgical treatment. The two most common sources of information used by patients were written material from surgeons (199/268–74%) and the Internet (184/268–69%). There was a trend for women who chose bilateral mastectomy to use the Internet more frequently than those choosing unilateral mastectomy ( P = 0.056). Number of surgeons consulted, genetic testing, and MRI were significant predictors of patient choice of mastectomy over breast-conserving therapy. Multivariate analysis showed that the number of surgeons consulted ( P < 0.001) and genetic testing ( P < 0.001) were independent predictors of choosing mastectomy, whereas MRI was not. In conclusions, understanding factors driving patient decision-making may promote more effective education for patients requiring breast cancer surgery.